Fetal and Perinatal Deaths in Aspect of Forensic Medicine - Atılmış, Ümit Ünüvar; Akgül, Esin; Müsellim, Nurşen Turan; Süner, Çiğdem; Gürpınar, Süleyman Serhat (The Bulletin of Legal Medicine, 2003)
Evaluation of fetal and perinatal deaths in forensic medicine have difficulties. Fetal and perinatal reports of The First Specialization Department of the Council of Forensic Medicine were retrospectively reviewed between 2000 and 2004 years to determinate the criteria needed for diagnosis. The scene of death, sex, gestational age, explanations, registration of judicial report, histopathological and toxicological reports and judicial questions were reviewed in 119 reports. Used criteria in report for diagnosis was determinated and discussed.